USE OF SWIRLERS IN HEAT EXCHANGERS (Conferencea, 2022)
Shell and tube heat exchangers are one of the most common types of equipment in the chemical and oil refining industries and account for a quarter of all process equipment. Therefore, at present, shell-and-tube heat exchangers of increased thermal efficiency are of great interest on the part of the industry. This is due to the desire to increase the output of manufactured products, reduce the number of heat exchangers for transferring the same amount of heat, and reduce the cost of maintenance and repair of equipment. One of the structural elements that increase the thermal efficiency of shell-and-tube heat exchangers are ring swirlers.